British Imperialism in the Punjab, 1845-58: An Appraisal - Fouzia Umar (JSSH, 2023)
The British came late to the Punjab and stayed there for almost a century. After the first Anglo Sikh War (1845) the Trans-Sutlej territories of Jullundur and Hoshiarpur were annexed by the British. A Regency Council was established under a British Resident in Lahore to govern the remainder of the Sikh Kingdom. The collapse of this arrangement led to the Second Anglo-Sikh War (1849) and decisive victory of the British in the battle of Gujrat paved the way of British annexation of the Punjab. The Punjab in the years to come provided a firm foundation to the British imperialism in India. The Punjab episode under the British rule is considered comparatively a period of relative peace and stability. When the British, after a century of turbulence, took the control of the Punjab they brought political and socio-economic transformation. Dalhousie’s scheme of administration in Punjab at the time of its annexation was combined with the advantages of both the civil and a military government. The triumvirate (Board of Administration) laid the foundation of effective governance and imperialism in the Punjab and later on the Punjab as the Chief Commissioner’s province (from 1853 onwards) consolidated the imperial structures in the Punjab. Peace and reforms in the initial years earned popularity and goodwill for the British in the Punjab